Damned good piseiro! - de Souza , Fernando Antonio Ferreira (Seven Editora, 2023)
Under the media understanding of the forró variant, the piseiro emerges today as a fluent expression in discourses of representativeness of popular and globalized, northeastern and national culture. Its use tends to supply images, imaginaries and symbolic values that nourish the cultural industry more than emic identifiers of tradition of its practitioners and aficionados. Its transient, emblematic and politically articulated character for mass consumption lays bare the decolonial problematic (QUIJANO, 2005), which involves its emergence and use. Fruit of collaborative ethnographic methodology, under domains of a dialogical ethnomusicology, this article contemplates a reflective approach from the crossing of testimonies and testimonies that structure sound discourses of the music of the piseiro.DOI:https://doi.org/10.56238/alookdevelopv1-046